Impact of Nigella sativa meal on blood metabolites and immune status of growing lambs - Nasr, Heba A.; Eldeeb, Fares A.; Ahmed, Abdelbaset; Abdel-Raheem, Ghada S.E. (Journal of Advanced Veterinary Research, 2025)
The aim of the present study was to assess the impact of Nigella sativa meal (NSM) at different levels of inclusion on blood metabolites, antioxidant status and immunomodulatory of growing lambs. Thirty-five Rahmani lambs were randomly allocated to five diet treatments for 90 days. Group 1 received a basal diet without Nigella sativa meal and considered as control, while groups 2, 3, 4 and 5 fed on diets contained 6, 12, 18 and 24 % NSM, respectively. The parameters measured were blood metabolites, oxidative stress indicators, immune response, and inflammatory cytokines levels. Blood metabolites indicated increased total protein, albumin, and globulin levels, while the levels of creatinine, liver enzymes, lipids, and glucose were reduced. There were increases in antioxidants and immune markers and a decrease in inflammatory markers. It could be concluded that supplementation of NSM enhance blood metabolites, antioxidant status, and immune status of growing Rahmani lambs and therefore, suggests the use of NSM as a sustainable and ideal alternative for antibiotics.